Binocular Vision: The Effect of Induced Prisms in Haploscopic Measurement of Fusional Limits - Sheni, D D (Canadian Journal of Optometry, 1983)
When the haploscope is used to measure fusional limits at near, a -2.50 D lens is placed in a lens holder in front of each eye of the subject. It is assumed that the lines of sight will rotate equal amounts to the movement of the haploscope tubes such that the foveal fixation is maintained. This assumption is investigated. It was found that the lines of sight of 60% of the subjects studied lagged behind the movement of the arms of the haploscope. The implication of this is discussed and it is recommended that the haploscope be used as an instrument to train fusional vergences rather than to measure them.